Supply continuity planning - Zsidisin, George A. (Henry Stewart Talks, 2011)
Supply chain disruptions, Supplier disruption sources, Market/industry disruption sources, Business continuity planning defined, Supply continuity planning framework, Awareness, Prevention, Risk assessment, Supply risk assessment, Risk assessment attributes, Remediation, Major stages of a disruption, Knowledge management